The effects of Zn and Yb co-dopants on the electronic, radiation shielding, structural, thermal and spectroscopic properties of hydroxyapatite - Ayhan, Yasemin Merve; Ates, Tankut; Seckin, Turgay; Ozcan, Imren; Bulut, Niyazi; Kurucay, Ali; Kaygili, Omer (Elsevier, 2024)
This work presents a comprehensive investigation of the electronic properties of hydroxyapatite (HA) doped with zinc (Zn) and ytterbium (Yb). Four different compositions, namely 0.33Zn-0.33Yb-HA, 0.33Zn-0.66Yb-HA, 0.66Zn-0.33Yb-HA, and 0.66Zn-0.66Yb-HA, were studied using Density of States (DOS) and band structure calculations. The computed band gap values for each composition were determined to be 4.3097 eV, 4.1324 eV, 4.2527 eV, and 4.2088 eV, respectively. The observed decrease in the band gap energy from 0.33Zn-0.33Yb-HA to 0.66Zn-0.66Yb-HA signifies a significant impact of the dopant composition on the electronic properties of the material. Furthermore, the inclusion of ytterbium in the HA matrix resulted in the formation of a distinct band and peak in the density of states. This indicates the emergence of specific energy levels associated with Yb, suggesting a distinct influence on the electronic structure of the material. These findings provide valuable insights into the tunability of the electronic properties of HA through controlled doping with Zn and Yb. Such knowledge is crucial for tailoring materials with desired electronic characteristics, thus holding promise for various applications in electronic devices and biocompatible coatings. The as-modeled structures were synthesized via a wet chemical route. Fourier transform infrared (FTIR), Raman, and X-ray diffraction (XRD) analyses verified the formation of the HA structure for each sample. Differential thermal analysis (DTA) results showed that all the as-prepared samples were thermally stable. The negligible mass losses were detected for all the samples in the thermogravimetric analysis (TGA) measurements. The addition of both co-dopants affected crystal structure related parameters and decreased the crystallinity and cell viability.
Keywords: Hydroxyapatite; Zn-Yb doping; Density of states; Band structure; Electronic properties